Total CAD/CAM Supported Method for Manufacturing Removable Complete Dentures - Arthur Furtado de Mendonça; Mario Furtado de Mendonça; George Shelby White; Georges Sara; Darren Littlefair (Hindawi Limited, 2016)
The incorporation of computer-aided design/computer-aided manufacturing (CAD/CAM) technology into complete denture fabrication brings about several advantages to the fabrication process, providing better predictability of the desired outcomes and high accuracy of denture fit, mainly because the milling of prepolymerized acrylic resin eliminates the shrinkage of the acrylic base. Also, there is a decrease in the porosity when compared to a conventionally processed denture, and consequently there is a decrease in the retention of Candida albicans on the denture base. The presented workflow for complete denture fabrication presents a totally wax-free manufacturing process, combining rapid prototyping (RP) and rapid milling. With the presented technique, the maxillomandibular relation (MMR) and the ideal setup of the tooth arrangement are developed by using occlusion rims and trial setup made with RP. For the definitive final denture, the denture base and the basal surfaces of the conventional denture teeth were milled according to the individual clinical situation. Posteriorly, the teeth were adapted and bonded into the milled sockets of the milled base.